The geography of prescription pharmaceuticals supplied to the USA: levels, trends, and implications. Issue 1 (29th January 2021) - Shivdasani, Yashna; Kaygisiz, Neriman Beste; Berndt, Ernst R; Conti, Rena M
Abstract: Prescription pharmaceuticals are frequently used consumer products whose manufacturing location is commonly held as a trade secret by firms and US regulatory agencies. Here we use previously non-publicly available data to describe levels and trends in the manufacturing locations of the most commonly used prescription pharmaceuticals, off-patent generic drugs, intended to be consumed by Americans. We find that the base ingredients required for the manufacturing of these prescription drugs are overwhelmingly and increasingly manufactured in non-domestic locations, specifically India and China. The manufacturing of finished prescription drugs for the American market is more equally split between domestic and foreign locations, but is increasingly foreign as well. The American reliance on non-domestic manufacturing of prescription drugs is important for stakeholders to appreciate, given current quality and pricing concerns and their potential susceptibility to interruptions in supply due to natural disasters, pandemics, and international trade negotiations. We discuss implications of these levels and trends for current domestic and international policy discussions.